Targeting a Hidden Enemy: Pyriproxyfen Autodissemination Strategy for the Control of the Container Mosquito Aedes albopictus in Cryptic Habitats. - Kshitij Chandel; Devi Shankar Suman; Yi Wang; Isik Unlu; Eric Williges; Gregory M Williams; Randy Gaugler (Public Library of Science (PLoS), 2016)
BACKGROUND:The Asian tiger mosquito, Aedes albopictus, is a vector of dengue, Chikungunya, and Zika viruses. This mosquito inhabits a wide range of artificial water-holding containers in urban and suburban areas making it difficult to control. We tested the hypothesis that female-driven autodissemination of an insect growth regulator could penetrate cryptic oviposition habitats difficult to treat with conventional insecticidal sprays. METHODOLOGY:Oviposition preferences of Ae. albopictus females for open and cryptic cups were tested in semi-field experiments. Two conventional larvicidal sprayers were tested to determine droplet penetration and larvicidal efficacy in open and cryptic habitats using Bacillus thuringiensis var. israelensis (Bti) in the field. Finally, the efficacy of pyriproxyfen autodissemination stations was assessed in cryptic and open cups in residential areas during 2013 and 2014. PRINCIPAL FINDINGS:Gravid females strongly preferred cryptic (53.1±12.9 eggs/cup) over open (10.3±4.3 eggs/cup) cups for oviposition. Cryptic cups showed limited droplet penetration and produced 0.1-0.3% larval mortality with a conventional backpack and low-volume sprays of Bti. The autodissemination stations effectively contaminated these cryptic cups (59.3-84.6%) and produced 29.7-40.8% pupal mortality during 2013-2014. Significant pupal mortality was also observed in open cups. CONCLUSIONS:The autodissemination station effectively exploits the oviposition behavior of wild gravid females to deliver pyriproxyfen to targeted oviposition habitats. Although the pupal mortality in cryptic cups was relatively lower than expected for the effective vector control. Autodissemination approach may be a suitable supporting tool to manage Ae. albopictus immatures in the cryptic habitats those are less accessible to conventional larvicidal sprays.